A hyphal fusion mutant in Neurospora crassa - J F Wilson; Jo Ann Dempsey (Fungal Genetics Reports, 1999)
Hyphal anastomoses are common in filamentous fungi, and they have been described in detail. Little information beyond descriptions is available. These descriptions indicate that the process is complex, and probably involves the activity of several genes. We describe a mutant of Neurospora crassa in which hyphal fusions cannot be found. It has no other morphological abnormalities. To our knowledge it is the first of its class.